2019
DOI: 10.1002/imhj.21773
|View full text |Cite
|
Sign up to set email alerts
|

Examining program quality in early childhood home visiting: From infrastructure to relationships

Abstract: Although there are many examples of evidence‐based early childhood home‐visiting programming, the field itself struggles with modest outcomes and variable levels of program effectiveness. This article documents the experience of creating a statewide monitoring system to assess home‐visiting program quality and compliance to identified standards, integrating multiple sources of information across different domains of functioning. Monitoring results from 57 programs are summarized, with variable but promising le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…For example, while a number of studies have found that more visits or longer enrollment periods lead to more positive outcomes (e.g., Green, Sanders, & Tarte, ; Raikes et al., ), other studies have found that parenting interventions that are shorter in duration may be more effective (Bakermans‐Kranenburg, van IJzendoorn, & Juffer, ; Pinquart & Teubert, ). Similarly, studies have not found consistent evidence that structural indicators align well with aspects of process quality such as the quality of the home visitor–family relationship, satisfaction with services, or family motivation to engage with services (Goldberg, Bumgarner, & Jacobs, ; Kormacher, Frese, & Gowani, this issue; Riley, Brady, Goldberg, Jacobs, & Easterbrook, ). The current state of the home‐visiting research in this area provides little clear guidance regarding the relative importance of these frequently used measures of fidelity and, therefore, how much weight they should be given in defining quality services.…”
Section: The Need For Conceptual Clarity: What Is Quality?mentioning
confidence: 99%
“…For example, while a number of studies have found that more visits or longer enrollment periods lead to more positive outcomes (e.g., Green, Sanders, & Tarte, ; Raikes et al., ), other studies have found that parenting interventions that are shorter in duration may be more effective (Bakermans‐Kranenburg, van IJzendoorn, & Juffer, ; Pinquart & Teubert, ). Similarly, studies have not found consistent evidence that structural indicators align well with aspects of process quality such as the quality of the home visitor–family relationship, satisfaction with services, or family motivation to engage with services (Goldberg, Bumgarner, & Jacobs, ; Kormacher, Frese, & Gowani, this issue; Riley, Brady, Goldberg, Jacobs, & Easterbrook, ). The current state of the home‐visiting research in this area provides little clear guidance regarding the relative importance of these frequently used measures of fidelity and, therefore, how much weight they should be given in defining quality services.…”
Section: The Need For Conceptual Clarity: What Is Quality?mentioning
confidence: 99%
“…Although HVPs have proved their efficacy in helping children and families at risk ( Avellar and Supplee, 2013 ; Peacock et al., 2013 ), the statistical power level seems to suggest small to modest, albeit positive, effect sizes ( Bilukha et al., 2005 ; Sweet and Appelbaum, 2004 ). Therefore, it is important to understand these incongruities in order to increase the benefits of HVPs ( Guterman et al., 2018 ; Korfmacher et al., 2019 ; LeCroy and Lopez, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, it may be stated that home-visiting programs that present specific characteristics may contribute to long-term benefits for both the child and the mothers ( Korfmacher et al., 2019 ; Sama-Miller et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the home‐visiting field takes advantage of the HOVRS as one of the very few psychometrically sound measures of home‐visiting quality (Design Options for Home Visiting Evaluation, ), the definition of quality remains a conundrum for the field. Korfmacher, Frese, and Gowani (this issue) distinguish between fidelity, compliance, and quality, though state that all three are critical to measure in home‐visiting programs. Korfmacher et al.…”
mentioning
confidence: 99%